Evaluating the impact of context-sensitivity on Andersen's algorithm for Java programs. - Liang, Donglin
Program analysis and program optimization of Java programs require reference information that estimates the instances of classes that may be accessed through dereferences. Recent work has presented several approaches for adapting Andersen's algorithm [1]---the most precise flow-insensitive and context-insensitive points-to analysis algorithm developed for C--- for analyzing Java programs (e.g., [5, 9, 12]). Studies in our previous work [6] indicate that this algorithm may compute very imprecise reference information for Java programs.
Keywords: Software; Programming languages; Language classifications; Object oriented languages; Software Engineering; Software / Program Verification; Metrics; Performance measures; Processors; Optimization; Design; Theory; Verification